PENGARUH LAMA PERENDAMAN DENGAN MENGGUNAKAN LARUTAN DAUN SALAM (SZYGIUM POLYANTHUM) SEBAGAI PENGAWET TERHADAP TOTAL PLATE COUNT DAN SALMONELLA DAGING BROILER - Barus, Joyevan Giba; Santosa, Purnama Edy; Septinova, Dian (Jurnal Riset dan Inovasi Peternakan, 2017)
The aim of research to determine the content of total plate count and Salmonella in broiler meat which is immersed in salam leaf solution.  This research was conducted in Mei—June 2017.  The analysis was done in Veterinary Public Health laboratory, Lampung Regional Veterinary Hall.  This research used 20 chicken sample that collected from poultry farm then slaughtered and immersed in salam leaf solution.  The results of this research indicated that from 20 chicken sample, the P0 treatment (without immersed in salam leaf solution) contain lesser average Total Plate Count level compared P1 (20 minutes), P2 (40 minutes), P3 (60 minutes). Only P0 treatment that contain amount of Total Plate Count below the maximum microba contamination standard while other treatments contain Total Plate Count above the maximum microba contamination standard.  The results of research in Salmonella content indicated negatif results in every treatments. Key words: broiler meat, salam leaf, salmonella and total plate count.